Effect of COVID-19 Pandemic on Emergency Service Suicide Applications in a Tertiary Psychiatric Clinic in Türkiye - Buket Koparal; Mehmet Ünler; Hande Gazey; Berfu Ünal; Hatice Cansu Selvi; Selçuk Candansayar (Gazi Medical Journal)
Objective: During the COVID-19 pandemic, several studies have reported increased suicidality. The widespread negative impacts of the pandemic, such as the economic downturn, isolation, and quarantine, have contributed to the complex interaction of factors influencing suicidal behavior. This study aimed to compare the clinical characteristics of individuals with suicidal thoughts/attempts between the pandemic and the pre-pandemic period. Methods: This descriptive study retrospectively evaluated the data of patients between 2018 and 2022. The period from March 2020 to March 2022 was defined as the “pandemic period”, while the period from March 2018 to March 2020 was labeled as the “pre-pandemic period”. While 185 patients applied to the emergency department due to suicidal thoughts/attempts in the pre-pandemic period, the number of cases consulted during the pandemic was 150. Results: During the COVID-19 period, 21% of patients were evaluated due to suicidal thoughts/attempts. In the pre-pandemic period, this rate was approximately 20%. There was no statistical difference between the groups in terms of age, suicide method, or lifetime psychiatric diagnoses. The proportion of males who presented with suicidality during COVID-19 was significantly higher. Conclusion: Pandemics can create social trauma and increase suicide rates. Gender roles, such as men being more inclined to conceal their complaints and feeling more economically responsible, may have increased the rates of suicidality during the pandemic. The mental, physical, and social impacts of the pandemic should be assessed in this context, and necessary precautions and interventions should be planned.